Penyelesaian Sengketa Hak Asuh Anak Melalui Litigasi: Kajian Perkara No. 011/Pdt. G/2018/Pta. Plk - Neng Eri Sofiana (Program Studi Hukum Keluarga dan Hukum Ekonomi Syariah, Program Pascasarjana Institut Agama Islam Negeri (IAIN) Ternate, 2022)
The settlement of child custody disputes becomes an endless dispute, as in case no. 011/Pdt. G/2018/PTA. Plk previously had three decisions from different courts. Custody is one of the things fought over by married couples who are going to or are getting divorced. This paper will look at how the settlement of child custody disputes is resolved by litigation as in case no. 011/Pdt. G/2018/PTA. Plk, and how the settlement is out of court or non-litigation and what considerations are used to resolve the dispute. Written using literature study with primary sources in the form of laws and related regulations. As a result, the holder of child custody is prioritized to the mother, but the regulation does not clearly state this requirement, so this is one of the judges' considerations. The consideration of judges in court as well as parties who help resolve cases outside of litigation as a whole will rely on what is best for the child by considering all aspects.